An Insight to Automobile Safety Systems - H. Adarsha; K. Venkadeshwaran; J. Deepak; N. Beemkumar (New Approaches in Engineering Research Vol. 11, 2021)
Technology has boosted the auto industry’s innovation efforts. Road accidents are growing increasingly common and dangerous as a result of societal development accompanied by significant increase in vehicle sales. As the frequency of traffic accidents rises, so does the number of people getting killed in them in many cases. Accidents occur largely as a result of reckless driving, excessive speed, and other associated characteristics. Owing to this, there is a greater need to avoid traffic accidents and save human lives. At the same time, with the rapid development of science and technology, there has been tremendous improvement in the automotive technology and auto safety technology which is being gradually integrated into all aspects of cars. This chapter intends to present the main car safety technologies, which are available and some new technologies which are evolving for the safety of vehicle in order to reduce damage caused in road accidents. Active safety technologies which tend to avoid the accidents like antilock breaking system, Brake assist, forward collision warning system and lane departure warning system as well as passive safety technologies like seat belt, airbags, head rest and crumple zones which minimizes the damage after the collision has occurred are both discussed.